2021
DOI: 10.3390/nu13020339
|View full text |Cite
|
Sign up to set email alerts
|

Fractalkine, sICAM-1 and Kynurenine Pathway in Restrictive Anorexia Nervosa–Exploratory Study

Abstract: The link between the kynurenine pathway and immunomodulatory molecules—fractalkine and soluble intercellular adhesion molecule-1 (sICAM-1)—in anorexia nervosa (AN) remains unknown. Fractalkine, sICAM-1, tryptophan (TRP), kynurenine (KYN), neuroprotective kynurenic acid (KYNA), neurotoxic 3-OH-kynurenine (3-OH-KYN), and the expression of mRNA for kynurenine aminotransferases (KAT1-3) were studied in 20 female patients with restrictive AN (mostly drug-free, all during first episode of the disease) and in 24 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…In the presence of low fat stores, depleted glycogen, and insufficient Kcal intake, AN patients have to turn to release amino acids from the skeletal muscle back into the plasma. In the middle of these opposite results, other studies demonstrated that plasma Trp levels did not change comparing underweight AN patients and CTRs [ 56 ]. In our cohort, higher Trp value was registered for restricting and purging AN subtypes as well as BN patients and was positively correlated with excessive levels of physical activity, corroborating the catabolism hypothesis.…”
Section: Discussionmentioning
confidence: 92%
“…In the presence of low fat stores, depleted glycogen, and insufficient Kcal intake, AN patients have to turn to release amino acids from the skeletal muscle back into the plasma. In the middle of these opposite results, other studies demonstrated that plasma Trp levels did not change comparing underweight AN patients and CTRs [ 56 ]. In our cohort, higher Trp value was registered for restricting and purging AN subtypes as well as BN patients and was positively correlated with excessive levels of physical activity, corroborating the catabolism hypothesis.…”
Section: Discussionmentioning
confidence: 92%
“…Likewise, a cross-sectional study including 59 dialyzed patients, of which 13 manifested poor appetite and malnutrition, revealed that the plasma levels of free TRP, LNAA, and TRP/LNAA ratios were similar between anorectic and well-nourished patients [ 45 ]. Similarly, a study of 20 female patients with restrictive AN revealed no changes in serum TRP compared to 24 control individuals [ 53 ].…”
Section: Tryptophan and Kynurenines In Anorexia Nervosamentioning
confidence: 99%
“…KYNA deficiency normalized as the body weight increased [ 52 ]. A quarter of a century later, the peripheral levels of kynurenines were investigated in 20 female patients with restrictive AN (mostly drug-free, all during the first episode of the disease) and compared with 24 controls [ 53 ]. We detected neither changes in serum L-kynurenine, KYNA, nor in the ratios TRP/L-kynurenine or L-kynurenine/KYNA.…”
Section: Tryptophan and Kynurenines In Anorexia Nervosamentioning
confidence: 99%
See 2 more Smart Citations